The Dynamic Relationship between Tourism and Economy: Evidence from Nepal - Karki, Dipendra (Journal of Business and Management, 2018)
The objective of this paper is to analyse the role of tourism in the Nepalese economic growth. I use a trivariate model of real Gross Domestic Product (GDP), international tourist arrivals and real effective exchange rate to investigate the long-run and short-run relationship between tourism and economic growth. The Augmented Dickey-Fuller ( ADF) test is used to determine the order of integration of the series, and I employ the Engle- Granger cointegration procedure to test for the presence of long-run relationship. By using annual macroeconomic data for Nepal for the period of 1962-2011, results reveal that there is a cointegrating relationship between tourism and economic growth.